The Emergency Curriculum as a Solution of Students’s Learning Loss During the Pandemic - Madhakomala Madhakomala; Monja Asita Dewi; Sofiyah Azizah; Zahrah Ajeng Syachputri; Sidiq Nuhaq (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
Since the Covid-19 pandemic has spread in Indonesia, it has greatly affected every field of work, including education. The government issued a new policy regarding distance learning, where distance learning is one solution to prevent the acceleration of the spread of Covid-19. However, distance learning has several drawbacks and is considered less effective because students or teachers have to adapt in a short time. This causes concern for students to fall behind in learning, because online learning can show some shortcomings, such as students not being focused on learning, being lazy to take part in learning, increasing assignments, and so on. The existence of an emergency curriculum is expected to be a solution to this problem. So, the author formulated the purpose of writing this research article is to determine the effectiveness of the emergency curriculum as a solution for students' backwardness in learning during the pandemic. The type of research used in this articel is a literature review and research data were collected based on documentation data collection techniques. The results of the research are that during the pandemic, the potential for students to fall behind is increasingly evident. Especially the provinces located on the island of Papua, the Nusa Tenggara Islands, and the Maluku Islands. Implementation of the emergency curriculum can be used as a solution because this curriculum makes regulations by reducing the basic competencies of each subject. The conclusion is that the emergency curriculum gives educational institutions the freedom to design and implement the learning process based on the conditions of each school. The emergency curriculum is effective to be applied at all levels of education. The author suggests that with this emergency curriculum, educational institutions or educators can make good use of this curriculum and students will not experience learning backwards.